(untitled) (Journal of the College of Basic Education, 2022)
Dental caries is a localized, transmissible infectious process that ends up in the destruction of hard dental tissue. Streptococcus mutans is one of the main opportunist pathogen of dental caries which plays a central role in fermenting carbohydrates that result in acid production, leading to the corrosion of tooth enamel. In addition, other microflora like Lactobacillus species are also associated with active caries lesions. Punica granatum, which belongs to the family of Punicaceae has been used extensively as a traditional medicine in many countries for the treatment of dysentery, diarrhea, helminthiasis, acidosis, hemorrhage and respiratory infections.Four Streptococcus mutans, seven Lactobacillus acidophilus and two Candida albicans isolates were tested using well diffusion method in different dilutions 100% ,75% ,50% ,25% and 10% of Pomegranate juice.Streptococcus mutans isolates showed greatest effect while two Lactobacillus acidophilus isolates had no effect to all dilutions on the other hand all Candida albicans isolates revealed resistant to all Pomegranate juice dilutions.The results suggest that Pomegranate juice is an effective antimicrobial substance against bacteria like Streptococcus mutans and Lactobacillus acidophilus,while it has no effect on fungus like Candida albicans which they are major dental pathogens. Aim of this study was to determine antimicrobial activity of Pomegranate juice against Streptococcus mutans,Lactobacillus acidophilus and Candida albicans isolates which they are major dental pathogens.